The Development of System Dynamics Model to Increase National Sugar Fulfillment Ratio - Suryani, E.; Hendrawan, R.A.; Taufik, E.; Muhandhis, I.; Dewi, L.P. (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
Sugar is one of the basic needs for people and industries that currently still continues to be a problem due to lack of domestic production. There are 11 refined sugar factory companies with an installed capacity of 5 million tons. However, there is an idle capacity of refined sugar factory about 46%. In 2013, an estimated domestic market demand of crystal sugar was around 2.8 million tons, while total production of farmers and sugar factory was only 2.7 million tons. This could pose a risk of a surge in sugar prices at retail level. Without adequate protection, cane farmers and sugar factories in Indonesia will be harmed in the long run. We need to achieve self-sufficiency in sugar production by conducting land intensification and expansion in all parties starting from smallholder, government, and private industry. Therefore, we developed a set of system dynamics simulation models to increase the fulfillment ratio of sugar. System dynamic is a computer-aided framework to develop policy analysis and design. We utilized system dynamics framework based on consideration that this framework can accommodate the internal and external factors that have significant contribution to sugar fulfillment ratio. Based on the simulation results, the fulfillment ratio can be increased by conducting land expansion and intensification. With land expansion of around 40,000 ha per year for 15 years, government harvested area would be around 606,617 ha in 2030. Fulfillment ratio after land expansion and intensification would be greater than 1 starting from 2020.